First molecular detection of Borrelia sp. in tapirs (Tapirus terrestris) - Mongruel, Anna Claudia Baumel [UNESP]; Medici, Emília Patrícia; da Costa Canena, Ariel; Machado, Rosangela Zacarias [UNESP]; Clay, Keith; Labruna, Marcelo Bahia; André, Marcos Rogério [UNESP] (Springer Nature, 2024)
Borrelia theileri is a tick-borne spirochete causative agent of fever, apathy and reduced food consumption in cattle. Molecular diagnosis has expanded the understanding of Borrelia theileri with new hosts and geographical locations being described. The present study aimed to describe the first molecular detection of B. theileri in wild tapirs (Tapirus terrestris) from South America. Blood DNA samples obtained from 99 tapirs sampled in Pantanal (n = 61) and Cerrado (n = 38) biomes were screened using a qPCR assay based on the 16 S rRNA gene of Borrelia sp. Positive samples in the qPCR assay were subjected to PCR assays to allow characterization of fragments from 16 S rRNA and flaB genes. Two (2/99; 2.0%) animals from Pantanal biome were positive in the qPCR and one sample presented bands of expected size for the flaB protocol. Amplicons from this sample were successfully cloned and sequenced. In the phylogenetic analysis, Borrelia sp. from T. terrestris grouped together with B. theileri sequences previously detected in Rhipicephalus microplus ticks and cattle from Minas Gerais State in Brazil, Rhipicephalus geigyi from Mali, and R. microplus and Haemaphysalis sulcata from Pakistan. This finding contributes to our knowledge regarding susceptible hosts species for B. theileri. More studies are necessary to understand the potential effects of B. theileri on tapir’s health.
Keywords: Borreliosis; PCR; South America; Spirochetes; Wildlife